RELATIONSHIP BETWEEN EDUCATION LEVEL AND ANXIETY IN MENOPAUSEE WOMEN IN RW V BAE VILLAGE, BAE DISTRICT, KUDUS REGENCY - Rina Novita; Tiara Fatma Kumala (LPPM AN NUUR, 2022)
Background: The quality of education in Indonesia was still relatively low, which was ranked 124th in the world out of 187 countries with an average educated population who did not graduate from elementary school. The results of a preliminary study in RW V Bae Village, from 10 people, 9 people were anxious, 6 people had elementary/junior high school education, 3 people had high school education and 1 person was not anxious. Objective: To analyze the relationship between education level and anxiety in menopause women in RW V Bae Village, Bae District, Kudus Regency.Research method: This type of research was quantitative with a correlation analytic research design, a cross sectional approach, the location and time of the study in Bae RW V Village in May-July 2021, the research population was 198, the number of samples used was 30 with purposive sampling technique. The instruments used were questionnaires and TMAS. The data analysis technique was processed with SPSS 16. Results: The results of the Fisher's Exact Test obtained the Asymp value. Sig. (2sided) 0,058 (0,058 > 0,05), it can be concluded that H0 is accepted, meaning there is no significant relationship between education level and anxiety in postmenopausal women in RW VBae Village, Bae District, Kudus Regency, as evidenced by RR= 1,714 (CI 95 %, 1,004-2,926).Conclusion: That the level of education does not affect anxiety due to family support and good activities.